Using discriminant analysis in adult education - Gary J. Conti (Adult Education Research Conference, 1993)
Discriminant analysis is a powerful multivariate statistical technique that has been used successfully in several recent adult education studies. This technique allows the researcher to divide the sample into meaningful groups which reflect real-life situations and to simultaneously analyze multiple variables that have the potential of explaining group placement.